Carboxylated Graphene: An Innovative Approach to Enhanced IgA-SARS-CoV-2 Electrochemical Biosensing - Luciana de Souza Freire; Ariamna María Dip Gandarilla; Yonny Romaguera Barcelay; Camila Macena Ruzo; Barbara Batista Salgado; Ana P. M. Tavares; Francisco Xavier Nobre; Julio Nino de Souza Neto; Spartaco Astolfi-Filho; Ștefan Țălu; Pritesh Lalwani; Niranjan Patra; et al. (Biosensors)
Biosensors harness biological materials as receptors linked to transducers, enabling the capture and transformation of primary biorecognition signals into measurable outputs. This study presents a novel carboxylation method for synthesizing carboxylated graphene (CG) under acidic conditions, enhancing biosensing capabilities. The characterization of the CG was performed using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), Raman spectroscopy, thermogravimetric analysis (TGA), and X-ray diffraction (XRD). We modified screen-printed carbon electrodes (SPCEs) with CG to immobilize the SARS-CoV-2 N-protein, facilitating targeted detection of IgA antibodies (IgA-SARS-CoV-2). The analytical performance was assessed via electrochemical techniques such as cyclic voltammetry and electrochemical impedance spectroscopy, confirming CG synthesis effectiveness and biosensor functionality. The developed biosensor efficiently detects IgA-SARS-CoV-2 across a dilution range of 1:1000 to 1:200 v/v in a phosphate-buffered saline (PBS) solution, with a limit of detection calculated at 1:1601 v/v. This device shows considerable potential because of its fast response time, miniaturized design facilitated by SPCEs, reduced sample volume requirements, high sensitivity and specificity, low detection limits, and signal enhancement achieved through nanomaterial integration.